Acute respiratory failure and mechanical ventilation in pregnant patient: A narrative review of literature - Pradeep Kumar Bhatia; Ghansham Biyani; Sadik Mohammed; Priyanka Sethi; Pooja Bihani (Wolters Kluwer Medknow Publications, 2016)
Physiological changes of pregnancy imposes higher risk of acute respiratory failure (ARF) with even a slight insult and remains an important cause of maternal and fetal morbidity and mortality. Although pregnant women have different respiratory physiology and different causes of ARF, guidelines specific to ventilatory settings, goals of oxygenation and weaning process could not be framed due to lack of large-scale randomized controlled trials. During the 2009 H1N1 pandemic, pregnant women had higher morbidity and mortality compared to nonpregnant women. During this period, alternative strategies of ventilation such as high-frequency oscillatory ventilation, inhalational of nitric oxide, prone positioning, and extra corporeal membrane oxygenation were increasingly used as a desperate measure to rescue pregnant patients with severe hypoxemia who were not improving with conventional mechanical ventilation. This article highlights the causes of ARF and recent advances in invasive, noninvasive and alternative strategies of ventilation used during pregnancy.